Strategi Komunikasi Penyiar Radio Sushi 99.1 Fm Dalam Mempertahankan Program Unggulan Pantun Balega Kepada Pendengar Loyal Di Kota Padang - Fareza, Rahmat; Flowerina, Indria (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
In the era of communication 5.0, technology is developing rapidly, causing radio to be less attractive to the younger generation. However, Radio Sushi FM, with the program "Pantun Balega", maintains its loyal listeners. The biggest challenge is the dependence on one broadcaster, One Tina. The research aims to understand Radio Sushi 99.1 FM's communication strategy in maintaining the program in Padang City.In this research, the method used is descriptive qualitative because it collects data in the form of words and pictures, not numbers. This approach produces descriptive data in the form of written or spoken words from people and observed behavior. Observation, interviews, and documentation were used for data collection. The research was conducted at Radio Sushi 99.1 FM, Padang, with key informants: General Manager and Program Director, as well as broadcasters of Pantun Balega program. Triangulation was used to ensure the validity of the data.Radio Sushi 99.1 FM's communication strategy in maintaining Pantun Balega program to loyal listeners in Padang City is based on media dependency theory. Through deep understanding of listeners, consistency of broadcast schedule, involvement in the community, and interactivity with listeners, Sushi FM builds strong and sustainable relationships, making it an irreplaceable source of information and entertainment.Radio Sushi 99.1 FM has successfully implemented effective broadcaster communication strategies in the Pantun Balega program, including deep understanding of listeners, consistency of broadcast schedule, involvement in the community, and interactivity with listeners. However, the main drawback is the lack of a substitute broadcaster for the program, leading to dependence on one broadcaster and potential losses during absences.